Uncovering the Healing Properties of Plumbago auriculata L. - Karishma Singh (Student's Journal of Health Research Africa, 2026)
Background: Plumbago auriculata L. is a medicinal plant widely used in traditional healing practices. Aim: This study aimed to identify the phytochemical constituents present in leaf extracts of P. auriculata and to evaluate their antibacterial activity. Setting: This experimental laboratory study used P. auriculata leaves collected in Durban, South Africa, in May 2023, followed by laboratory-based phytochemical and antibacterial analyses. Methods: Qualitative phytochemical screening and gas chromatography–mass spectrometry (GC–MS) were used to characterise bioactive constituents of the leaf extracts. Antibacterial activity was assessed against selected Gram-positive and Gram-negative bacteria using agar-based screening, with bacterial suspensions standardised to 0.5 McFarland. Results: GC–MS analysis of the methanolic leaf extract identified 50 compounds, with 13-docosenamide, hexadecanoic acid 2-hydroxy-1-(hydroxymethyl) ethyl ester, n-tetracosanol-1, 1,10-cycloicosanedione, and 5,7-dihydroxy-4-methylcoumarin among the major constituents. Qualitative screening showed multiple classes of secondary metabolites across the solvent extracts. The methanolic leaf extract showed antibacterial activity against the tested Gram-positive and Gram-negative bacteria. Conclusion: P. auriculata leaves contain diverse phytochemical constituents and demonstrate antibacterial potential, supporting further investigation of this species as a source of bioactive compounds. Recommendation: Future studies should include bioassay-guided isolation, cytotoxicity testing, mechanistic studies, and in vivo safety and efficacy assessments before therapeutic applications are considered.